Maria Montessori's Intercultural relevance: childhoods and languages in the educational context - Francesca Linda Zaninelli (University of Bologna, 2021)
This paper will explore some aspects of the Montessori method and pedagogy that are pertinent in rethinking today's increasingly interdependent and heterogeneous educational and school contexts (Zoletto, 2012). Personalized learning and differentiation are constant tensions in Montessori thinking, taking shape in the environment prepared by the adult specifically for each child, where the developmental materials offered are not conditioned by cultural affiliations (Pesci e Trabalzini, 2007) and linguistic plurality is a structural feature of the context (Consalvo, 2020), as occurs in many method schools that are experimenting with bilingual projects. According to Montessori (2000), children acquire language, habits and the characteristics of the community they are part of from the environment, and for this reason school environments and the relational atmospheres based on the uniqueness and differences of each individual are intercultural (Pesci, 2006). The paper offers some initial reflections starting from an investigation of Montessori's intercultural relevance in a multilingual perspective, one of the PRIN (2017) research areas Maria Montessori from the past to the present (Research Units: Bologna, Milan, Rome, Aosta).